El potencial relacional del Arteterapia en la intervención psicoterapéutica temprana de la psicosis - Reyes, Pamela (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2007)
This work describes and analizes the therapeutic process through art-therapy individual sesions in a young patient who develops a first psychotic episode. The process in the context of early intervention in psychosis shows how the psychotherapy trough the art, contributes in the building of therapeutic bonds in the therapeutic system.